Board Gender Diversity as a Moderator: ESG, Sustainability Reporting, and Green Innovation on Firm Value - Hidayat, Imam; Erdawati, Lena; Sukiranto, Sukiranto; Husin, Ng (International Journal of Energy Economics and Policy, 2026)
This study examines and analyzes the influence of Environmental, Social and Governance, Sustainability Reporting and Green Innovation on Firm Value with Board Gender Diversity as Moderation. This study uses a quantitative approach and secondary data. The population in this study are energy sector companies listed on the Indonesia Stock Exchange (IDX). The results of the study show that the independent variables, namely environmental, social and governance, sustainability reporting and green innovation with the moderating variable, namely board gender diversity, together have an influence on firm value. While partially environmental, social and governance has a positive effect on company value, sustainability reporting has a negative effect on company value, green innovation has no effect on firm value. Board gender diversity can moderate the influence of Environmental, Social and Governance and sustainability reporting on firm value. However, board gender diversity does not moderate the influence of green innovation on firm value. This study adds a moderating variable of board gender diversity, which is considered to have a combined influence on the relationship between Environmental, Social and Governance, sustainability reporting and green innovation on firm value which aims to answer the inconsistency of previous research findings.